2022
DOI: 10.48550/arxiv.2202.13615
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short term variability of DS Tuc A observed with TESS

Salvatore Colombo,
Antonio Petralia,
Giuseppina Micela

Abstract: Context. Impulsive short term variations occur in all kinds of solar-type stars. They are the results of complex phenomena such as the stellar magnetic field reconnection, low-level variability or in some cases even star-planet interactions. The radiation arising from these events is often highly energetic and, in stars hosting planets, may interact with the planetary atmospheres. Studying the rate of these energetic phenomena is fundamental to understand their role in modifying the chemical composition or, in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…By using the relationship between flare energy released in the optical band and in X-rays inferred by Flaccomio et al (2018) from the flares observed in the NGC 2264 young star forming region, this limit corresponds to X-ray energies of order of 10 31 erg. The flares we detected in the present XMM-Newton observation seem very rare events that likely released energies in the optical band in excess of 5 × 10 35 erg which are on the very high energy tail of the flare energies observed with TESS by Colombo et al (2022). Furthermore, in the optical band there is a significant fraction of pairs of flares separated by a few ks, similar to the separation of the two flares we observed in X-rays.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…By using the relationship between flare energy released in the optical band and in X-rays inferred by Flaccomio et al (2018) from the flares observed in the NGC 2264 young star forming region, this limit corresponds to X-ray energies of order of 10 31 erg. The flares we detected in the present XMM-Newton observation seem very rare events that likely released energies in the optical band in excess of 5 × 10 35 erg which are on the very high energy tail of the flare energies observed with TESS by Colombo et al (2022). Furthermore, in the optical band there is a significant fraction of pairs of flares separated by a few ks, similar to the separation of the two flares we observed in X-rays.…”
Section: Discussionsupporting
confidence: 79%
“…The energy released during the first and second flare are about 8 × 10 34 erg and 5 × 10 34 erg. Colombo et al (2022) used TESS light curves of DS Tuc to study the rate of flares of DS Tuc in the optical band with an analysis of all available sectors through an iterative method based on Gaussian processes. They found that the frequency of flares with energy (in optical band) larger than 2 × 10 32 erg amounts to about 2 per day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kavanagh et al (2021) found that, based on reconstructions of AU Mic's magnetic field and mass loss rate, AU Mic b could reside in the sub-Alfvénic regime. If this is true, flaring SPI is also possible (Lanza 2018); a recent study even claimed to have visually identified hints of such an interaction in TESS data (Colombo et al 2022). In fact, AU Mic is the most actively flaring star among all currently known exoplanet hosts (Ilin et al in prep.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, ∼15 TOI host stars have measured flare rates (e.g. Günther et al 2020;Pope et al 2021;Gilbert et al 2021;Bogner et al 2021;Colombo et al 2022). Most notably, Medina et al (2020) performed a flare search on all single low mass stars in the southern sky within 15 pc.…”
Section: Introductionmentioning
confidence: 99%